54 Residual risk in cardiac rehab: can we reduce-it more? Eligibility for icosapent ethyl in patients attending cardiac rehabilitation. (30th September 2020) - Gaine, S; Coughlan, JJ; Maher, V; Waters, M
Abstract : Introduction: Patients with elevated triglycerides (TG) are at increased risk for ischemic events despite statin therapy and controlled low-density lipoprotein cholesterol (LDL-C). The REDUCE IT trial showed that a highly purified Eicosapentaenoic acid (EPA) ester, Icosapent Ethyl or Ethyl Eicosapentaenoic acid (E-EPA), reduces the risk of ischemic events and cardiovascular (CV) death in patients with elevated TG levels despite statin therapy. The NNT for the first occurrence of major adverse cardiac events for the five-point primary composite endpoint was 21. E-EPA is also a dominant strategy from a cost-effectiveness perspective in the study. Thus, the 2019 ESC/EAS guidelines recommend E-EPA for patients with persistently raised TGs despite treatment with a statin. Our aim was to assess the proportion of patients attending cardiac rehabilitation who may benefit from E-EPA therapy as per REDUCE-IT trial criteria and the 2019 ESC/EAS guidelines. Methods: We prospectively collected data on all cardiac rehabilitation patients in our centre in 2018/2019. We then performed a hierarchal analysis of these patients to determine the percentage of patients post MI/CABG that would meet criteria for E-EPA as per REDUCE-IT trial criteria and ESC/EAS guidelines. = The REDUCE IT trial criteria were: ≥45 years and established ASCVD 50 years with DM and at least one other CV RF Fasting TG level of 1.69 to 5.63 mmol/L LDL–C level of 1.06 to 2.59 mmol/L Receiving a stable dose of a statin for at least 4 weeks The initial trial protocol enrolled patients with a TG level as low as 1.52 mmol/L to account for the 10% variability in TG levels. This protocol was amended and changed the lower level for TG to 2.26 mmol/L. We analysed patients as per both protocols. As per ESC: E-EPA 2 × 2 g per day should be considered in combination with a statin for patients with: Persistently high TGs (1.5–5.6 mmol/L) Treatment with a statin Results: 398 patients completed cardiac rehab during this study and were included in our database. Of these 275 (69%) had a 6 month TG and LDL recorded and were included. All patients in our cohort had been on a stable dose of statin for at least 4 weeks. Analysis as per initial REDUCE IT protocol: 14/275 patients (5%) were excluded as they were less than 45 years old. 63 patients (23%) had a TG level of 1.5–5.6 and 42 of these had an LDL-C level of 1.06–2.59 mmol/L (15.3%). This led to an overall eligibility of 15.3% for E-EPA. Analysis as per amended REDUCE-IT protocol: 14/275 patients (5%) were excluded as they were less than 45 years old. 30 patients had a TG level eligible as per the amended REDUCE-IT protocol (10.9%) and 20 of these patients had an LDL-C level of 1.06–2.59 mmol/L (7.3%) leading to an overall eligibility of 7.3% for E-EPA. Analysis as per the ESC/EAS guidelines: Notably the ESC guidelines do not specify an LDL level or age required for E-EPA to be considered. 64 patients had a TG level of 1.5–5.6 mmol/L despite statin therapy. As such, 64/275 patients (23.3%) of our cohort would be eligible for E-EPA. Conclusions: E-EPA is a dominant cost-effective strategy to reduce CV risk in patients with elevated TG levels despite statin therapy. Nearly one quarter (23.3%) of patients in our cohort would be suitable for E-EPA treatment in order to further reduce their CV risk. Rehab services should develop screening strategies to identify and treat patients eligible for E-EPA therapy.